The Conundrum of Tricuspid Regurgitation Grading - Go, Yun Yun; Dulgheru, Raluca; Lancellotti, Patrizio (Frontiers in Cardiovascular Medicine, 2018)
Findings from early percutaneous tricuspid intervention trials have shown that the severity of tricuspid regurgitation (TR) far exceeded the current definition of severe TR. Also, the improvement in the amount of TR following tricuspid intervention is not accounted for by the current definition of TR as different degrees of severity at the severe end was grouped under the same umbrella term of ‘severe’. There has been a recent call to expand the TR grading system, encompassing 2 more grades, namely ‘massive’ and ‘torrential’ TR, in the order of increasing severity. This seems appropriate as the patients enrolled in tricuspid intervention trials were found to have TR severity up to 2 grades above the current severe thresholds of effective regurgitant orifice area (EROA) 40 mm2, regurgitant volume (R Vol) 45 ml and vena contracta (VC) width 7 mm. The proposed grade of ‘massive’ is defined by EROA 60-79 mm2, R Vol 60-74 ml and VC 14-20 mm, while ‘torrential’ is defined by EROA ≥ 80 mm2, R Vol ≥75 ml and VC ≥21 mm. The grading of tricuspid regurgitation requires a comprehensive, multi-parametric approach. In particular, quantitative assessment of TR should be performed in patients who require serial monitoring and quantification of treatment effect.